《穿过寒冬拥抱你》与《门锁》电影中比喻修辞的使用分析 PENGGUNAAN GAYA BAHASA PERUMPAMAAN PADA FILM “EMBRACE AGAIN” DAN “DOOR LOCK” - Kesumawaty Wijaya (Journal of Language, Literature and Teaching, 2022)
This research was conducted using a qualitative descriptive research method. Data collection techniques were carried out using documentation techniques and data sources in this study were dialogue transcripts in the films Embrace Again and Door Lock. In examining this research, the theories used are the style of language theory and the theory of qualitative analysis. In the results of this study, there are 3 types of figurative language styles found in the film Embrace Again, namely 3 simile language styles, 7 metaphor language styles and 9 allusion language styles. In Door Lock, there are 2 types of figurative language styles, namely 1 metaphor language style and 2 allusion language styles. From these results it can be seen that the figurative language style found in these two films more often uses the Allusion style of language. Also, the reason for using figurative language style by the writer is influenced by the usage of subjective and objective environment, but the writer places more emphasis on the usage of language style by emphasizing the mood of the character.Keywords: Types of figurative language styles, Film, Embrace Again, Door Lock